PEDIATRIC BLEPHAROKERATOCONJUNCTIVITIS WITH DESCEMETOCELE AND CORNEAL NEOVASCULARIZATION : A CASE REPORT: Poster Presentation - Case Report - Resident - Fadia Ghaisani; Ismi Zuhria (Majalah Oftalmologi Indonesia, 2023)
Introduction : Blepharokeratoconjunctivitis is a chronic and recurrent inflammatory eyelid disorder that is commonly associated with secondary conjunctival and corneal involvement that is frequently underdiagnosed in children. The objective is to report a descemetocele and corneal neovascularization as severe complications of blepharokeratoconjunctivitis in children. Case Illustration : A five years old girl complained blackish lump in the right eye since a month ago. She also had a whitish spot in her eye since a year ago with redness, glare and watery. Three years ago she had a lump in the right eyelid and eye redness intermittently that was getting better with eye drop and history of allergy of house dust mites. Visual acuity (VA) in right eye was hand movement. Anterior segment of the right eye showed telangiectasis of palpebra, hyperemic conjunctiva, with neovascularization of entire surface of the cornea, descemetocele, leucoma and corneal thinning around descemetocele. We injected subconjunctival anti-vascular endothelial growth factor (VEGF) injection then we performed amniotic membrane transplantation. Follow-up 2 months post surgery we found VA was 2 m counting finger and the corneal neovascularization was reduced. Discussion : This case represents severe blepharokeratoconjunctivitis can cause some complications, from this patient we found corneal neovascularization and descemetocele. Anti-VEGF injection was to inhibit new blood formation in the patient’s cornea and the amniotic membrane transplantation was to manage the descemetocele. Conclusion : Pediatric blepharokeratoconjunctivitis and the complications associated with its treatment can be sight threatening. Early recognition of this disease entity and adequate management may arrest the disease process and may minimize visual morbidity.